A dual process approach to understanding prejudice toward Americans in Lebanon: An extension to intergroup threat perceptions and emotions. (March 2013) - Levin, Shana; Pratto, Felicia; Matthews, Miriam; Sidanius, Jim; Kteily, Nour
Using a stratified random sampling procedure, we interviewed 200 residents of Beirut, Lebanon and surrounding areas in order to test predictions of a dual process model of prejudice. We examined the role of social dominance orientation (SDO) and right-wing authoritarianism (RWA) in predicting prejudice toward Americans, mediating the relationships between personality dimensions and prejudice, and predicting intergroup emotions indirectly through intergroup threat perceptions. Three main findings emerged. First, whereas RWA was a positive predictor of prejudice toward Americans, SDO was a negative predictor. Second, RWA mediated a positive relationship between a social conforming personality and prejudice toward Americans; SDO mediated a negative relationship between a tough-minded personality and prejudice. Third, value threat perceptions mediated a positive relationship between RWA and feelings of disgust toward Americans; economic threat perceptions mediated a negative relationship between SDO and anger toward Americans. Applications and extensions of the dual process model in non-Western populations are discussed.